2010
DOI: 10.1194/jlr.r000232
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase signaling in the vertebrate retina

Abstract: This article is available online at http://www.jlr.org was established by Streb et al. ( 3 ) in their classic paper that showed elevations in IP 3 caused intracellular release of bound calcium. Subsequently, 1,2-DG was found to stimulate protein kinase C (PKC), a serine/threonine kinase that phosphorylates a number of cellular proteins ( 4 ). Activation of the PLC/PKC cascade affects a variety of cellular events, including secretion, phagocytosis, smooth muscle contraction, proliferation, neurotransmission, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 290 publications
(327 reference statements)
3
42
0
Order By: Relevance
“…IR deletion in photoreceptor cells caused increased sensitivity to light-induced photoreceptor degeneration (5). We previously reported that light induces tyrosine phosphorylation of the retinal IR and that this activation leads to the binding of phosphoinositide 3-kinase (PI3K) to rod outer segment (ROS) membranes (6) and the subsequent activation of Akt (7,8). More recently, we demonstrated that IR activation is mediated through the photobleaching of the G-protein-coupled receptor, rhodopsin, but not signaling through the phototransduction cascade (9).…”
mentioning
confidence: 99%
“…IR deletion in photoreceptor cells caused increased sensitivity to light-induced photoreceptor degeneration (5). We previously reported that light induces tyrosine phosphorylation of the retinal IR and that this activation leads to the binding of phosphoinositide 3-kinase (PI3K) to rod outer segment (ROS) membranes (6) and the subsequent activation of Akt (7,8). More recently, we demonstrated that IR activation is mediated through the photobleaching of the G-protein-coupled receptor, rhodopsin, but not signaling through the phototransduction cascade (9).…”
mentioning
confidence: 99%
“…37,39,103,[128][129][130] These studies have described various complications such as pericyte loss, acellular capillaries, basement membrane thickening, activated glial cells and inflammation occurring within the neurosensory retina. 37,39,103,129,130 Unfortunately, work in animal models do not progress to the proliferative phase of diabetic retinopathy. 125 The exact mechanism of how high glucose levels contribute to the vascular and neuronal complications seen in diabetic retinopathy are not well understood, needing additional investigations to fully understand the pathology of this disease from the onset to visual loss.…”
Section: Chapter 5 General Discussionmentioning
confidence: 99%
“…101 While our findings confirm our hypothesis of TNF-modulation in insulin receptor signaling, we also recognize that our findings could be the result of phosphatases such as PTP1B that were previously suggested by Rajala et al 2010 which would decrease insulin receptor activity leading to a decrease in Akt activity. 102,103 It is well know that insulin receptor mediates activation of caspase-3 by signaling through the PI3K/Akt pathway as well as the MAPK pathway. 102,103 Our future studies will focus more in detail on the relationship of the PI3K and MAPK pathways in retinal Müller cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations